2020
DOI: 10.1055/s-0040-1716914
|View full text |Cite
|
Sign up to set email alerts
|

Patient, Caregiver, and Provider Perceptions of Transition Readiness and Therapeutic Alliance during Transition from Pediatric to Adult Care in Epilepsy

Abstract: Transition from pediatric to adult health care is a time of high risk for adolescents and young adults (AYAs) with epilepsy. Our aims are to examine patient, caregiver, and provider perceptions of transition readiness and the influence of patient-provider alliance in the context of transition readiness. Our cross-sectional study included 82 AYAs with epilepsy prior to transition. Patients, caregivers, and providers completed questionnaires (e.g., transition readiness and working alliance). Statistical analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Since parents are the principal healthcare agents for their sons affected by epilepsy, the examination of their perceptions of the transition from pediatric to adult healthcare is needed to develop effective and orchestrated plans for healthcare management [31]. A previous study showed that caregivers and patients differently perceive transition readiness, suggesting the importance of evaluating both transition experiences [32]. Some authors suggested that families of children with epilepsy experience high levels of stress during the parental role transition [33].…”
Section: Introductionmentioning
confidence: 99%
“…Since parents are the principal healthcare agents for their sons affected by epilepsy, the examination of their perceptions of the transition from pediatric to adult healthcare is needed to develop effective and orchestrated plans for healthcare management [31]. A previous study showed that caregivers and patients differently perceive transition readiness, suggesting the importance of evaluating both transition experiences [32]. Some authors suggested that families of children with epilepsy experience high levels of stress during the parental role transition [33].…”
Section: Introductionmentioning
confidence: 99%